PENELITIAN RIJAL AL-HADIS SEBAGAI KEGIATAN IJTIHAD - Mukhtar, Mukhlis (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2011)
Rijal al-Hadith is a Hadith reference for scholars and researchers tradition in researching the series-a series of narrators of hadith, especially in terms of linkage and sanad, quality and personal integrity of the narrators of Islamic teachings, intellectual capacity and various other information related to the research sanad Hadith. Research sanad of hadith are very closely related to the activities of ijtihad, because both activities require seriousness, sincerity, perseverance, precision and caution. Because of a tradition established its status is one of the sources of Islamic teachings, so the quality is very need to know in relation to the proof's traditions studied. The use of traditions that do not qualify will be able to lead the Islamic teachings do not correspond with what is supposed to be.